Elucidating the mechanism of action of novel lactams on Pseudomonas aeruginosa - Pantalone, P. (2019)
Biofilms are complex structures derived from the aggregation of bacteria in suspension or anchored to a surface. Due to their intrinsic biocide and antibiotic resistance, biofilm development and dispersal in healthcare, industrial and domestic environments represent a constant challenge. In bacteria such as Pseudomonas aeruginosa, biofilm maturation depends in part on quorum sensing (QS), a cell-to-cell communication system. This can be intercepted, thereby preventing, inhibiting or sensitizing biofilms to antimicrobials. Several natural compounds and their synthetic analogues successfully accomplish this strategy by targeting specific QS pathways. The pursuit of anti-biofilm agents as compatible as possible with the widest range of environments and applications has led to the development of new compounds for biofilm control based on the furanones produced by red algae. The aims of this project were to elucidate the mechanisms of action of a series of lactams related to the furanones and to describe how they perturb biofilm development in bacteria including P. aeruginosa, Staphylococcus aureus and Proteus mirabilis. For P. aeruginosa, reporter gene fusions, in silico, iso-thermal titration calorimetry, circular dichroism spectroscopy, protein crystallization and X-ray diffraction studies have revealed that the most potent compound inhibit 2-alkyl-4-quinolone (AQ) dependent quorum sensing by binding to and inhibiting the response regulator protein, PqsR. Transcriptome analysis confirmed these observations and uncovered additional potential targets involved in cell motility, RNA processing and biofilm development which were validated using reporter gene fusions and phenotypic assays. Different biofilm assays unexpectedly showed an increase of biomass in P. aeruginosa when the lead lactam was present at high concentrations in the growth medium. Furthermore, studies of P. mirabilis and S. aureus unveiled the potent inhibitory properties of the lead lactam on biofilm development on the former and significant growth inhibitory effects on the latter. In conclusion, the results of this work provide new insights into the mode of action of the lactams and suggest strategies for future development and application.